The Phenomenon of Slang Language Usage Among Gen Z on the X (Twitter) Platform - Rahmawati, Rahmawati; Rahayu, Abeliya; Budiyawati, Feby Amanda; Hilda, Afila; Julianti, Ulfah (Sean Institute, 2025)
This study explores the phenomenon of slang usage among Generation Z (Gen Z) in online communication interactions through the X application. In the context of technological advancements and the rise of social media, language has undergone significant changes in both form and function. The aim of this research is to describe the forms of slang used by Gen Z, to understand its function in digital communication, and to analyze its impact on the preservation of standard Indonesian. This study employs a qualitative descriptive method, with data collected through non-participant observation of Gen Z user posts on the X application. The results indicate that the slang used includes abbreviations, shortened forms, and code-mixing. This type of language is used not only for communication but also as a form of identity expression, lifestyle, and resistance against formal language norms. The study reflects the crucial role of social media in shaping language dynamics and underscores the importance of linguistic awareness in preserving standard Indonesian amidst the forces of globalization.